(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
One of the most significant tools for project planning and management is the Critical Path Method (CPM), as well as the Project Evaluation and Review Technique (PERT). When the time required or anticipated to perform specific activities is unclear, PERT is a project management method. CPM is a method for planning activities in which the amount of time required to accomplish the project is presently known. CPM is a step-by-step project management strategy that keeps processes and projects on track by focusing on important tasks. The Critical Route is the shortest approach to finish any project by following one path across all connected operations. The goal of this research is to examine the whole bullet train project, its critical activities and interdependencies, as well as the precedence connection between them. The authors of this research article examine the use of CPM and PERT calculations on bullet train projects. Using CPM we are studying the critical activities which can affect the project completion and using PERT authors are analyzing the estimated time for project completion.